2008
DOI: 10.2746/042516408x322175
|View full text |Cite
|
Sign up to set email alerts
|

The effects of maternal health and body condition on the endocrine responses of neonatal foals

Abstract: Disturbances in neonatal pancreatic beta cell function programmed during pregnancy may predispose foals to metabolic problems in later life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 41 publications
3
33
1
3
Order By: Relevance
“…This finding is in contrast to previous studies which suggested that equine offspring size and development did not alter with maternal obesity or overnutrition [8][9][10]. In the present study, mares were fed by the stud aiming to maintain a stable BCS, whereas in all previous studies mares of normal BCS have been fed to induce obesity during gestation [8,48]. In the present study, mares were fed by the stud aiming to maintain a stable BCS, whereas in all previous studies mares of normal BCS have been fed to induce obesity during gestation [8,48].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This finding is in contrast to previous studies which suggested that equine offspring size and development did not alter with maternal obesity or overnutrition [8][9][10]. In the present study, mares were fed by the stud aiming to maintain a stable BCS, whereas in all previous studies mares of normal BCS have been fed to induce obesity during gestation [8,48]. In the present study, mares were fed by the stud aiming to maintain a stable BCS, whereas in all previous studies mares of normal BCS have been fed to induce obesity during gestation [8,48].…”
Section: Discussioncontrasting
confidence: 99%
“…Increased foal birthweight may have important consequences. In horses, maternal nutrition and fetal overgrowth has been associated with altered insulin function in the neonatal period [13,48,52,53]. In horses, maternal nutrition and fetal overgrowth has been associated with altered insulin function in the neonatal period [13,48,52,53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, cardiovascular function, glucose homeostasis and endocrine function were altered until weaning [612]. Despite the fact that severe maternal undernutrition at mid-gestation related to an infection with Streptococcus equi was shown in one study to induce intra-uterine growth retardation (IUGR) [13], most other studies on effects of maternal nutrition indicate that moderate maternal nutritional excess or undernutrition in gestation does not affect birthweight [1418]. Nevertheless, excess maternal nutrition during pregnancy, with or without carbohydrate supplementation, can affect glucose and lipid metabolism in foals until 160 days of age [13,15,17].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that severe maternal undernutrition at mid-gestation related to an infection with Streptococcus equi was shown in one study to induce intra-uterine growth retardation (IUGR) [13], most other studies on effects of maternal nutrition indicate that moderate maternal nutritional excess or undernutrition in gestation does not affect birthweight [1418]. Nevertheless, excess maternal nutrition during pregnancy, with or without carbohydrate supplementation, can affect glucose and lipid metabolism in foals until 160 days of age [13,15,17]. Moreover, an epidemiological study performed in Belgium in a large cohort of horses demonstrated that the incidence of osteochondrosis (OC) is higher in foals born to dams fed concentrates during gestation compared to foals whose dams received forage only [19].…”
Section: Introductionmentioning
confidence: 99%